What school will you go to? (Journal of Parents and Teachers, 2017)
The Family-School Connection is fundamental in the development of the child's personality. Although parents are primarily responsible for the education of their children, the educational community as a whole should contribute to the overall education of the student.
Keywords: educational community; association; school council; educational contract; internal regulations; school rules and policies; school identity; educational project